The effect of the role-playing model on speaking skills in Indonesian language learning for fifth grade Students at SDN 1 Tegalsambi Jepara - Synthia, Lukistyani; Munir, Muhammad Misbahul; Wiranti, Dwiana Asih (Mitra PGMI: Jurnal Kependidikan MI, 2025)
Effective Indonesian language learning is crucial for developing students' speaking proficiency. Preliminary observations at SDN 1 Tegalsambi revealed suboptimal speaking skills attributable to several instructional limitations, particularly the predominant use of conventional teacher-centered methods. The Role-Playing model emerges as a promising innovative approach to enhance learning outcomes through active student engagement. This study examines: (1) differences in speaking skills before and after Role-Playing implementation, and (2) the model's degree of influence on speaking skill development among fifth-grade elementary students. Employing a quantitative pre-experimental design (One Group Pretest-Posttest), the research sampled all 36 fifth-grade students at SDN 1 Tegalsambi Jepara through saturation sampling. Speaking skills were assessed using performance rubrics, with data analyzed via Paired Sample T-Tests and regression analysis in IBM SPSS Statistics. Results demonstrated significant improvement (p < 0.001), with mean scores increasing from 67.31 (pretest) to 80.78 (posttest). The regression model (R² = 0.728) indicates the Role-Playing approach explains 72.8% of variance in speaking skill enhancement.